The racial constitution of neoliberalism. (July 2021) - Kundnani, Arun
Prevailing scholarship on neoliberalism fails to recognise that it generates its own distinctive forms of racial domination. Influential analysts such as Wolfgang Streeck, David Harvey and Wendy Brown assume or argue that racism exists today because neoliberalism's defeat of racial legacies is incomplete. This ignores how racism is reconfigured in ways that are specific to the historical moment of neoliberalism and dependent on a distinctive and substantial intellectual and political hinterland. A consideration of Friedrich Hayek's theory of cultural evolution reveals a contradiction in neoliberal thought between its aspiration to establish a universal market system and its dependence on particularist ideas of western cultural pre-eminence. This ideological contradiction correlates with the fact that globalisation produces masses of surplus populations which are of no market value. A racial idea of culture is the means by which neoliberalism manages and works through its own limitations. Above all, 'race' provides a means of coding and managing the material boundaries between different forms of labour under neoliberalism: citizen and migrant, waged and 'unexploitable', bearers of entitlements and bare life.